Complex abdominal wall reconstruction in the setting of active infection and contamination: a systematic review of hernia and fistula recurrence rates. (3rd April 2017) - Hodgkinson, J. D.; Maeda, Y.; Leo, C. A.; Warusavitarne, J.; Vaizey, C. J.
Abstract: Aim: Minimal evidence exists to guide surgeons on the risk of complications when performing abdominal wall reconstruction (AWR) in the presence of active infection, contamination or enterocutaneous fistula. This study aims to establish the outcomes of contaminated complex AWR. Method: Analysis was conducted according to PRISMA guidelines. Systematic search of the MEDLINE, EMBASE and Pubmed databases was performed. Studies reporting exclusively on single‐staged repair of contaminated complex AWR were included. Pooled data were analysed to establish rates of complications. Results: Sixteen studies were included, consisting of 601 contaminated complex AWRs, of which 233 included concurrent enterocutaneous fistula repair. The average follow‐up period was 26.7 months. There were 146 (24.3%) reported hernia recurrences. When stratified by repair method, suture repair alone had the lowest rate of recurrence (14.2%), followed by nonabsorbable synthetic mesh reinforcement (21.2%), biological mesh (25.8%) and absorbable synthetic mesh (53.1%). Hernia recurrence was higher when fascial closure was not achieved. Of the 233 enterocutaneous fistula repairs, fistula recurrence was seen in 24 patients (10.3%). Suture repair alone had the lowest rate of recurrence (1.6%), followed by nonbiological mesh (10.3%) and biological mesh reinforcement (12%). Forty‐six per cent of patients were reported as having a wound‐related complication and the mortality rate was 2.5%. Conclusion: It is feasible to perform simultaneous enterocutaneous fistula repair and AWR as rates of recurrent fistula are comparable with series describing enterocutaneous fistula repair alone. Hernias recurred in nearly a quarter of cases. This analysis is limited by a lack of comparative data and variability of outcome reporting.